Preparation method and application of high-concentration nitrogen-doped graphene aerogel material
By doping high-concentration nitrogen atoms in graphene and using nickel oxide to catalyze urea decomposition, an efficient formaldehyde adsorption material was prepared, which solved the problem of poor formaldehyde removal effect in the prior art, and achieved efficient and rapid formaldehyde adsorption effect.
Patent Information
- Application Number
- CN202510157807.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-02-13
AI Technical Summary
The prior art is difficult to efficiently remove formaldehyde, and commonly used adsorbents such as activated carbon and bamboo carbon have problems such as weak chemical adsorption capacity, limited adsorption capacity and prone to desorption.
By doping high-concentration nitrogen atoms in graphene, using nickel oxide to catalyze urea decomposition to produce ammonia, improving nitrogen doping efficiency, and preparing high-concentration nitrogen-doped graphene aerogel materials through high-frequency ultrasonic mixing, hydrothermal reaction and other steps.
It significantly improves the short-term rapid adsorption capacity of graphene aerogel to formaldehyde, improves the nitrogen content and specific surface area, enhances the formaldehyde adsorption effect, and is simple and easy to use, suitable for industrial large-scale production.
Smart Images

Figure CN119909650A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of air purification material preparation, and in particular relates to a preparation method and application of a high-concentration nitrogen-doped graphene aerogel material. Background Art
[0002] Formaldehyde is a major indoor air pollutant, usually released from building materials, furniture products, coatings and other organic substances. In indoor environments, high concentrations of formaldehyde can cause serious damage to the human respiratory system, nervous system and immune system. In fact, even low concentrations of formaldehyde may have adverse effects on human health. Therefore, in order to minimize the harm of formaldehyde to the human body, it is particularly important to develop efficient gas adsorption materials to remove formaldehyde.
[0003] At present, the commonly used formaldehyde removal method on the market is to use adsorbents such as activated carbon or bamboo charcoal bags. However, these adsorbents have obvious limitations. Due to their weak chemical adsorption ability and limited adsorption capacity, they cannot quickly adsorb formaldehyde and are prone to desorption. This not only affects the effect of air purification, but may also cause secondary pollution of the environment. In contrast, graphene materials show good application prospects in formaldehyde adsorption. In particular, by doping graphene with heteroatoms such as nitrogen (N), sulfur (S), and phosphorus (P), its chemical adsorption capacity can be significantly improved and the occurrence of desorption can be reduced. Among them, nitrogen atom doping has received widespread attention because of its more mature preparation process and potential for industrial application.
[0004] However, in order to obtain graphene materials with high concentrations of nitrogen doping, many studies have used amino-containing chemicals as nitrogen sources. These substances are usually toxic and costly, and are not suitable for large-scale production. In contrast, urea is an abundant, low-toxic and nitrogen-rich substance, and is an ideal nitrogen source. Although using urea as a nitrogen source can load nitrogen atoms on graphene, thereby improving its chemical adsorption capacity for formaldehyde, it is difficult to achieve high-concentration nitrogen doping at low urea dosage. This limits its effectiveness and economy in practical applications. Summary of the invention
[0005] The present invention aims to overcome the defects of the prior art and provide a method for preparing a high-concentration nitrogen-doped graphene aerogel material.
[0006] Another object of the present invention is to provide an application of the high-concentration nitrogen-doped graphene aerogel material prepared by the above preparation method.
[0007] The technical solution of the present invention is as follows:
[0008] A method for preparing a high-concentration nitrogen-doped graphene aerogel material comprises the following steps:
[0009] (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing, and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture;
[0010] (2) adding the nickel oxide-urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution;
[0011] (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material.
[0012] In a preferred embodiment of the present invention, in step (1), the mass ratio of urea to nickel oxide is 100-1000:1.
[0013] Further preferably, the concentration of the ethanol aqueous solution is 30-70%.
[0014] More preferably, the mass ratio of the nickel oxide to the ethanol aqueous solution is 5-50:9995-9950.
[0015] In a preferred embodiment of the present invention, in step (2), the mass ratio of the nickel oxide-urea mixture to graphene oxide is 1-10:1.
[0016] Further preferably, in the graphene oxide aqueous solution, the concentration of graphene oxide is 0.2-1 wt.%.
[0017] In a preferred embodiment of the present invention, in step (3), the temperature of the hydrothermal reaction is 160-200° C. and the time is 8-24 h.
[0018] Further preferably, the freeze-drying time is 24-72 hours.
[0019] The high-concentration nitrogen-doped graphene aerogel material prepared by the above preparation method is used in the preparation of formaldehyde adsorption material.
[0020] A formaldehyde adsorption material, the raw material of which includes the high-concentration nitrogen-doped graphene aerogel material prepared by the above preparation method.
[0021] The beneficial effects of the present invention are:
[0022] 1. The present invention uses urea as a nitrogen source, which has the advantages of abundant content, low cost, and rich nitrogen. Under the catalytic hydrolysis of nickel oxide, urea can produce more ammonia to participate in the reaction during the hydrothermal process, thereby significantly improving the nitrogen conversion rate of urea, and further expanding the application scope of urea as a nitrogen source in the preparation of air purification materials.
[0023] 2. The present invention first mixes urea and nickel oxide in an ethanol aqueous solution, and prepares a mixture of urea and nickel oxide by rapid freezing. This method can effectively prevent nickel oxide from precipitating during a long freezing process, thereby ensuring that the two are mixed evenly. This provides favorable conditions for nickel oxide to fully catalyze the hydrolysis of urea in the graphene oxide aqueous solution.
[0024] 3. The mixed treatment of urea and nickel oxide in ethanol aqueous solution in the present invention is necessary and beneficial, mainly based on the dispersibility of urea and nickel oxide in different solvents. Compared with directly adding nickel oxide and urea to graphene oxide aqueous solution, it is difficult to achieve a good catalytic effect due to the poor dispersibility of nickel oxide in water and insufficient contact with urea. Although the dispersibility of nickel oxide is improved by directly adding nickel oxide and urea to graphene oxide ethanol aqueous solution, ethanol may react with urea or its decomposition products at high temperature in the hydrothermal reaction, reducing the nitrogen doping efficiency and even affecting the morphology and structure of graphene, which is not conducive to the doping effect.
[0025] 4. The process flow of the present invention is simple, easy to operate, green, efficient, and low in energy consumption, and is suitable for large-scale industrial production and application. The preparation method can significantly increase the specific surface area of the graphene aerogel and increase the nitrogen atom content of urea doped in the graphene aerogel, thereby greatly improving its short-term rapid adsorption capacity for formaldehyde. Compared with the nitrogen-doped graphene aerogel prepared without adding nickel oxide as a catalyst, the nitrogen content of the high-concentration nitrogen-doped graphene aerogel material obtained by the present invention is increased by more than 35%, and its formaldehyde adsorption effect within 10 minutes is increased by more than 60%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The total specific surface area and micropore area data of the high-concentration nitrogen-doped graphene aerogel material prepared in Example 5 of the present invention and the nitrogen-doped graphene aerogel material prepared in Comparative Example 5 are shown.
[0027] Figure 2 The N atom content of the high-concentration nitrogen-doped graphene aerogel material prepared in Example 5 of the present invention and the nitrogen-doped graphene aerogel material prepared in Comparative Example 6 are shown. DETAILED DESCRIPTION
[0028] The technical solution of the present invention is further illustrated and described below through specific implementation modes in combination with the accompanying drawings.
[0029] Example 1
[0030] (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture; the mass ratio of nickel oxide to ethanol aqueous solution is 5:9995; the concentration of ethanol aqueous solution is 30%; and the mass ratio of urea to nickel oxide is 100:1;
[0031] (2) adding the nickel oxide urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of the nickel oxide urea mixture to the graphene oxide is 10:1; and the concentration of the graphene oxide in the graphene oxide aqueous solution is 0.2 wt.%;
[0032] (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 200° C.; the time of the hydrothermal reaction is 8 h; and the time of the freeze-drying is 24 h.
[0033] Example 2
[0034] (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture; the mass ratio of nickel oxide to ethanol aqueous solution is 10:9990; the concentration of ethanol aqueous solution is 60%; and the mass ratio of urea to nickel oxide is 1000:1;
[0035] (2) adding the nickel oxide urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of the nickel oxide urea mixture to the graphene oxide is 8:1; and the concentration of the graphene oxide in the graphene oxide aqueous solution is 0.5wt.%;
[0036] (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 16 h; and the time of the freeze-drying is 60 h.
[0037] Example 3
[0038] (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing, and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture; the mass ratio of nickel oxide to ethanol aqueous solution is 20:9980; the concentration of ethanol aqueous solution is 70%; and the mass ratio of urea to nickel oxide is 300:1;
[0039] (2) adding the nickel oxide urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of the nickel oxide urea mixture to the graphene oxide is 3:1; and the concentration of the graphene oxide in the graphene oxide aqueous solution is 0.8wt.%;
[0040] (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 160° C.; the time of the hydrothermal reaction is 24 h; and the time of the freeze-drying is 36 h.
[0041] Example 4
[0042] (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture; the mass ratio of nickel oxide to ethanol aqueous solution is 50:9950; the concentration of ethanol aqueous solution is 40%; and the mass ratio of urea to nickel oxide is 800:1;
[0043] (2) adding the nickel oxide urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of the nickel oxide urea mixture to the graphene oxide is 1:1; and the concentration of the graphene oxide in the graphene oxide aqueous solution is 1.0 wt.%;
[0044] (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 12 h; and the time of the freeze-drying is 72 h.
[0045] Example 5
[0046] (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture; the mass ratio of nickel oxide to ethanol aqueous solution is 10:9990; the concentration of ethanol aqueous solution is 50%; and the mass ratio of urea to nickel oxide is 100:1;
[0047] (2) adding the nickel oxide urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of the nickel oxide urea mixture to the graphene oxide is 10:1; and the concentration of the graphene oxide in the graphene oxide aqueous solution is 0.5wt.%;
[0048] (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 160° C.; the time of the hydrothermal reaction is 12 h; and the time of the freeze-drying is 48 h.
[0049] Comparative Example 1
[0050] (1) adding urea to a graphene oxide aqueous solution and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of urea to graphene oxide is 10:1; and the concentration of graphene oxide in the graphene oxide aqueous solution is 0.2 wt.%;
[0051] (2) subjecting the graphene oxide mixed solution obtained in step (1) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 200° C.; the time of the hydrothermal reaction is 8 h; and the time of the freeze-drying is 24 h.
[0052] Comparative Example 2
[0053] (1) adding urea to a graphene oxide aqueous solution and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of urea to graphene oxide is 8:1; and the concentration of graphene oxide in the graphene oxide aqueous solution is 0.5 wt.%;
[0054] (2) subjecting the graphene oxide mixed solution obtained in step (1) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 16 h; and the time of the freeze-drying is 60 h.
[0055] Comparative Example 3
[0056] (1) adding urea to a graphene oxide aqueous solution and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of urea to graphene oxide is 3:1; and the concentration of graphene oxide in the graphene oxide aqueous solution is 0.8 wt.%;
[0057] (2) subjecting the graphene oxide mixed solution obtained in step (1) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 160° C.; the time of the hydrothermal reaction is 24 h; and the time of the freeze-drying is 36 h.
[0058] Comparative Example 4
[0059] (1) adding urea to a graphene oxide aqueous solution and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of urea to graphene oxide is 1:1; and the concentration of graphene oxide in the graphene oxide aqueous solution is 1.0 wt.%;
[0060] (2) subjecting the graphene oxide mixed solution obtained in step (1) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 180° C.; the time of the hydrothermal reaction is 12 h; and the time of the freeze-drying is 72 h.
[0061] Comparative Example 5
[0062] (1) adding urea to a graphene oxide aqueous solution and mixing thoroughly to obtain a graphene oxide mixed solution; the mass ratio of urea to graphene oxide is 10:1; and the concentration of graphene oxide in the graphene oxide aqueous solution is 0.5 wt.%;
[0063] (2) subjecting the graphene oxide mixed solution obtained in step (1) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 160° C.; the time of the hydrothermal reaction is 12 h; and the time of the freeze-drying is 48 h.
[0064] Comparative Example 6
[0065] (1) adding urea and nickel oxide to a graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; the mass ratio of urea to nickel oxide is 100:1; the mass ratio of urea to graphene oxide is 10:1; the concentration of graphene oxide in the graphene oxide aqueous solution is 0.5wt.%;
[0066] (2) subjecting the graphene oxide mixed solution obtained in step (1) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a nitrogen-doped graphene aerogel material; the temperature of the hydrothermal reaction is 160° C.; the time of the hydrothermal reaction is 12 h; and the time of the freeze-drying is 48 h.
[0067] The N atom content in the high concentration nitrogen-doped graphene aerogel materials prepared in Examples 1-5 and the nitrogen-doped graphene aerogel materials prepared in Comparative Examples 1-5 was tested, and the results are shown in Table 1:
[0068] Table 1 N atom content in samples prepared in Examples 1-5 and Comparative Examples 1-5
[0069]
[0070] The samples prepared in Examples 1-5 and Comparative Examples 1-5 were respectively subjected to formaldehyde adsorption. The conditions for adsorbing formaldehyde were exactly the same, and the adsorption time was 10 min. The removal effects obtained were shown in Table 2:
[0071] Table 2 Effect of removing formaldehyde by samples prepared in Examples 1-5 and Comparative Examples 1-5
[0072]
[0073]
[0074] It can be seen from Table 1 and Table 2 that the preparation method of the present invention uses nickel oxide as a catalyst, which can catalyze the decomposition of urea to produce more ammonia for doping reaction, thereby improving the nitrogen conversion rate of urea and increasing the N atom content in the graphene aerogel, thereby increasing the ability of the graphene aerogel to quickly adsorb formaldehyde in a short period of time.
[0075] Figure 1 The total specific surface area and micropore area data of the high concentration nitrogen-doped graphene aerogel material prepared in Example 5 of the present invention and the nitrogen-doped graphene aerogel material prepared in Comparative Example 5 are shown. Figure 1 It can be seen that the preparation method of the present invention uses nickel oxide to catalyze the decomposition of urea to produce more ammonia, which can form pores in graphene oxide, thereby increasing the total specific surface area and micropore area of the graphene aerogel.
[0076] Figure 2 The N atom content of the high-concentration nitrogen-doped graphene aerogel material prepared in Example 5 of the present invention and the nitrogen-doped graphene aerogel material prepared in Comparative Example 6 is shown. Figure 2 It can be seen that the preparation method of the present invention pre-mixes nickel oxide and urea, which helps to improve the catalytic effect of nickel oxide on urea in the subsequent preparation process, thereby increasing the N atom content in the graphene aerogel.
[0077] The above description is only a preferred embodiment of the present invention, and therefore cannot be used to limit the scope of the present invention. That is, equivalent changes and modifications made according to the patent scope of the present invention and the contents of the specification should still fall within the scope of the present invention.
Claims
1. A method for preparing a high-concentration nitrogen-doped graphene aerogel material, characterized in that: The steps include: (1) fully mixing nickel oxide and ethanol aqueous solution by high-frequency ultrasound, adding urea to the ethanol aqueous solution containing nickel oxide, stirring and mixing, and rapidly freezing, and then freeze-drying to obtain a nickel oxide-urea mixture; (2) adding the nickel oxide-urea mixture obtained in step (1) to the graphene oxide aqueous solution, and mixing them thoroughly to obtain a graphene oxide mixed solution; (3) subjecting the graphene oxide mixed solution obtained in step (2) to a hydrothermal reaction, and finally washing and freeze-drying to obtain a high-concentration nitrogen-doped graphene aerogel material.
2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of urea to nickel oxide is 100-1000:
1.
3. The preparation method according to claim 2, characterized in that: The concentration of the ethanol aqueous solution is 30-70%.
4. The preparation method according to claim 3, characterized in that: The mass ratio of the nickel oxide to the ethanol aqueous solution is 5-50:9995-9950.
5. The preparation method according to claim 1, characterized in that: In the step (2), the mass ratio of the nickel oxide urea mixture to graphene oxide is 1-10:
1.
6. The preparation method according to claim 5, characterized in that: In the graphene oxide aqueous solution, the concentration of graphene oxide is 0.2-1wt.%.
7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (3), the temperature of the hydrothermal reaction is 160-200° C. and the time is 8-24 hours.
8. The preparation method according to claim 7, characterized in that: The freeze-drying time is 24-72h.
9. Use of the high-concentration nitrogen-doped graphene aerogel material prepared by the preparation method according to any one of claims 1 to 8 in preparing formaldehyde adsorption materials.
10. A formaldehyde adsorption material, characterized in that: The raw material comprises a high-concentration nitrogen-doped graphene aerogel material prepared by the preparation method described in any one of claims 1 to 8.
Citation Information
Patent Citations
Nano nickel oxide / graphene composite electrode material as well as preparation method and application thereof
CN102522218A
Graphene / cobalt oxide composite air purification material and preparation method thereof
CN109926022A
Preparation method of MgAl-LDH-loaded amino-functionalized graphene aerogel
CN115634628A
Preparation method and application of porous nitrogen-doped graphene aerogel material
CN118637603A
3D ruthenium / graphene aerogel composite loaded with metal-organic frameworks, preparation method thereof, and its application in continuous treatment of co
US20190126236A1
Cited By
Preparation method and application of high-concentration nitrogen-doped graphene aerogel material synthesized based on surface regulation
CN120838306A